First person - Kim Landry-Truchon and Nicolas Houde (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Kim Landry-Truchon is first author on 'Deletion of Yy1 in mouse lung epithelium unveils molecular mechanisms governing pleuropulmonary blastoma pathogenesis', published in DMM. Kim is a research assistant in the lab of Lucie Jeannotte at Centre de recherche du CHU de Québec-Université Laval, Québec, Canada, investigating organ development and the regulatory networks involved. Nicolas is a research assistant in the same lab, investigating the role of master transcription factors during mouse development.